Some Existence and Convergence Theorems for Nonexpansive Type Mappings. (10th January 2013) - Mishra, S. N.; Pant, Rajendra; Panicker, R.
Abstract : Some existence and convergence theorems for a class of nonexpansive type mappings are obtained in a normed space. The results obtained herein generalize certain known results.